Method for producing FeOHSO4 particles, positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery

By controlling the firing process of iron sulfate hydrate to promote FeSO4 incorporation into the FeOHSO4 crystal structure, the method enhances battery capacity in lithium ion batteries.

JP7609103B2Active Publication Date: 2025-01-07TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022044264
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-18
Publication Date
2025-01-07
Estimated Expiration
2042-03-18

AI Technical Summary

Technical Problem

Existing lithium ion batteries require improvements in battery capacity.

Method used

A method for producing FeOHSO4 particles involves firing a hydrate of iron sulfate at a controlled heating rate of 3.0°C/min or less and a maximum temperature of 400°C or less, promoting FeSO4 penetration into the crystal structure and suppressing its generation, thereby enhancing the discharge capacity of the particles.

Benefits of technology

The produced FeOHSO4 particles exhibit high discharge capacity when used as a positive electrode active material, leading to improved lithium ion secondary battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609103000002
    Figure 0007609103000002
  • Figure 0007609103000003
    Figure 0007609103000003
  • Figure 0007609103000004
    Figure 0007609103000004
Patent Text Reader

Abstract

To provide a method of producing a FeOHSO4 particle, a FeOHSO4 particle as a positive electrode active material of an improved battery capacity, and a lithium ion secondary battery of an improved battery capacity.SOLUTION: The production method according to the present disclosure, includes a step of firing an iron sulfate hydrate at a rate of temperature increase of 3.0°C / min or less and at a peak temperature of 400°C or less. A positive electrode active material of a lithium ion secondary battery is of a composition represented by FeOHSO4, wherein a ratio (Ib / Ia) of a peak intensity (Ib) at 33.5°≤2θ<34.5° relative to a peak intensity (Ia) at 34.5°≤2θ≤35.5° in an XRD spectrum obtained with CuKα rays is 0.43 or less. In the lithium ion secondary battery according to the present disclosure, a positive electrode body layer contains the positive electrode active material.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing FeOHSO4 particles, a cathode active material for a lithium-ion secondary battery, and a lithium-ion secondary battery.

Background Art

[0002] Patent Document 1 discloses a cathode active material for a lithium secondary battery, which has a composition represented by the general formula FeOHSO4 and has a particle diameter of 700 nm or less.

[0003] Patent Document 2 discloses a cathode active material for a lithium secondary battery, which has a composition represented by the general formula Fe 1-x M x OHSO4 (in formula (1), M is a transition metal element other than Fe, and x is a number satisfying 0 < x < 1.), and a lithium secondary battery including a cathode including the cathode active material.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0005] In a lithium-ion battery, it is required to improve the battery capacity.

[0006] As a cathode active material used in a lithium-ion battery, a cathode active material having a composition represented by the general formula FeOHSO4 is known.

[0007] The present disclosure aims to provide a method for producing FeOHSO4 particles, FeOHSO4 particles as a positive electrode active material with improved battery capacity, and a lithium ion secondary battery with improved battery capacity. [Means for solving the problem]

[0008] The present inventors have found that the above object can be achieved by the following means: Aspect 1 A method for producing FeOHSO4 particles, comprising the step of calcining iron sulfate hydrate at a heating rate of 3.0°C / min or less and at a maximum temperature of 400°C or less. Aspect 2 2. The method of claim 1, wherein the ferrous sulfate hydrate is ferrous sulfate heptahydrate. Aspect 3 The method according to aspect 1 or 2, wherein the firing step includes maintaining the temperature for 10 hours to 300 hours after raising the temperature to the maximum temperature. Aspect 4 The method according to aspect 3, wherein the maximum temperature is within a range of 100°C to 300°C. Aspect 5 The method according to any one of aspects 1 to 4, wherein the firing step is carried out in an air atmosphere. Aspect 6 The FeOHSO4 particles have a peak intensity (I a ) for the peak intensity at 33.5°≦2θ<34.5° (I b ) ratio (I b / I a 6. The method of any one of the preceding aspects, wherein the n-th order is less than 0.430. Aspect 7 7. The method according to any one of aspects 1 to 6, wherein the FeOHSO4 particles are a positive electrode active material for a lithium ion secondary battery. Aspect 8 It has a composition represented by the general formula FeOHSO4, and in X-ray diffraction measurement using CuKα radiation, the peak intensity at 34.5°≦2θ≦35.5° (I a) for the peak intensity at 33.5°≦2θ<34.5° (I b ) ratio (I b / I a ) is less than 0.430. Aspect 9: A lithium ion secondary battery, wherein a positive electrode active material layer contains the positive electrode active material according to embodiment 8. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide a method for producing FeOHSO4 particles, FeOHSO4 particles as a positive electrode active material with improved battery capacity, and a lithium ion secondary battery with improved battery capacity. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram of a lithium-ion secondary battery 1 according to a first embodiment of the present disclosure. [Diagram 2] FIG. 2 is a graph showing X-ray crystal diffraction (XRD) spectra of the FeOHSO4 particles of Example 1, Example 5, and Comparative Example 1. [Diagram 3] FIG. 3 is a graph showing the relationship between Ib / Ia and the discharge capacity of a lithium ion secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0012] <Production method of FeOHSO4 particles> The manufacturing method of the present disclosure is a method for producing FeOHSO4 particles, which includes a step of calcining iron sulfate hydrate at a heating rate of 3.0°C / min or less and a maximum temperature of 400°C or less.

[0013] The FeOHSO4 particles produced by the method of the present disclosure can be used as a positive electrode active material having a high discharge capacity.

[0014] Without being limited by theory, the FeOHSO4 particles produced by the production method of the present disclosure have a high discharge capacity for the following reasons.

[0015] FeOHSO4 particles can be obtained by calcining iron sulfate hydrate, for example, iron sulfate heptahydrate. During the calcination, the iron sulfate hydrate is dehydrated, and some of the OH is incorporated into the FeSO4 crystals to produce FeOHSO4. However, depending on the calcination conditions, a rapid desolvation reaction may occur, and OH may not be sufficiently incorporated into the FeSO4 crystals, making it easy for anhydrous FeSO4 to be produced.

[0016] The formation of FeSO4 reduces the discharge capacity of the FeOHSO4 particles.

[0017] In the manufacturing method of the present disclosure, iron sulfate hydrate is calcined at a heating rate of 3° C. / min or less and a maximum temperature of 400° C. or less. This promotes the penetration of OH into FeSO4 crystals. In other words, the production of FeSO4 is suppressed.

[0018] Therefore, the FeOHSO4 particles produced by the production method of the present disclosure have a high discharge capacity.

[0019] <Ferrous sulfate hydrate> The manufacturing method of the present disclosure includes calcining iron sulfate hydrate under predetermined conditions.

[0020] The hydrate of iron sulfate can be, for example, iron sulfate heptahydrate, which can be represented by the general formula FeSO4·7H2O.

[0021] <Firing process> The manufacturing method of the present disclosure includes a step of firing at a heating rate of 3.0°C / min or less and a maximum reaching temperature of 400°C or less.

[0022] The temperature rise rate in the firing step is 3.0° C. / min or less.

[0023] If the heating rate is 3.0° C. / min or less, the intrusion of OH into the FeSO4 crystals during firing is promoted, and the production of anhydrous FeSO4 is suppressed.

[0024] The heating rate may be 3.0° C. / min or less, 2.0° C. / min or less, 1.5° C. / min or less, 1.0° C. / min or less, or 0.5° C. / min or less, and may be greater than 0.0° C. / min, 0.1° C. / min or more, 0.5° C. / min or more, 1.0° C. / min or more, or 1.5° C. / min or more.

[0025] The starting temperature for heating in the baking step is not particularly limited, but may be, for example, room temperature, i.e., 25°C.

[0026] The maximum temperature reached in the calcination step is 400°C or less. The maximum temperature may be any temperature at which the iron sulfate hydrate is calcined and a dehydration reaction occurs, and more specifically, may be, for example, a temperature in the range of 100°C to 400°C. The maximum temperature may be 100°C or more, 150°C or more, 200°C or more, or 250°C or more, and may be 400°C or less, 300°C or less, 290°C or less, 280°C or less, or 270°C or less. The maximum temperature may be a temperature in the range of 100°C to 300°C.

[0027] The firing step may include, after raising the temperature to the maximum temperature, maintaining the temperature at the maximum temperature for a certain period of time, for example, 10 hours to 300 hours.

[0028] The time for maintaining the maximum reached temperature may be 10 hours or more, 25 hours or more, 50 hours or more, 75 hours or more, or 90 hours or more, and may be 300 hours or less, 250 hours or less, 200 hours or less, 150 hours or less, or 125 hours.

[0029] The firing step may be carried out, for example, in an air atmosphere.

[0030] <FeOHSO4 particles> The FeOHSO4 particles produced by the production method of the present disclosure have a peak intensity (I a ) for the peak intensity at 33.5°≦2θ<34.5° (I b ) ratio (I b / I a ) may be less than 0.43.

[0031] The peak intensity at 34.5°≦2θ≦35.5° (I a ) is the maximum value of the peak observed at 34.5°≦2θ≦35.5°. Similarly, the peak intensity (I b ) is the maximum value of the peak observed at 33.5°≦2θ<34.5°.

[0032] Here, "I a " is a peak derived from the crystal plane orientation (-122) of FeOHSO4. b " is a peak derived from the (200) crystal plane orientation of FeSO4.

[0033] (I b / I a ) means that there are fewer FeSO4 structures relative to the FeOHSO4 structures in the FeOHSO4 particles.

[0034] (I b / I a FeOHSO4 particles having an I of less than 0.430 have a high discharge capacity as a positive electrode active material. b / I a ) is less than 0.430, (I b / I a ) is 0.430 or more, (I b / I a ) becomes smaller, the discharge capacity tends to increase in particular.

[0035] (I b / I a ) may be less than 0.430 to 0.000 or more. b / Ia ) may be less than 0.430, 0.420 or less, 0.300 or less, 0.250 or less, or 0.100 or less, and may be 0.000 or more, 0.001 or more, 0.005 or more, or 0.010 or more.

[0036] The FeOHSO4 particles produced by the manufacturing method of the present disclosure have a high discharge capacity when used as a positive electrode active material for a lithium ion secondary battery. Therefore, the FeOHSO4 particles produced by the manufacturing method of the present disclosure are particularly suitable for use as a positive electrode active material for a lithium ion secondary battery.

[0037] 《Cathode active material》 The positive electrode active material of the present disclosure has a composition represented by the general formula FeOHSO4, and in X-ray diffraction measurement using CuKα radiation, has a peak intensity (I a ) for the peak intensity at 33.5°≦2θ<34.5° (I b ) ratio (I b / I a ) is 0.43 or less.

[0038] The positive electrode active material of the present disclosure may be FeOHSO4 particles produced by the production method of the present disclosure, and therefore, for its configuration, reference can be made to the above “<FeOHSO4 particles>”.

[0039] Lithium-ion secondary battery In the lithium ion secondary battery of the present disclosure, the positive electrode active material layer contains the positive electrode active material of the present disclosure.

[0040] When the lithium ion secondary battery of the present disclosure is a liquid-based lithium ion secondary battery, the lithium ion secondary battery can have a structure in which, for example, a positive electrode collector layer, a positive electrode active material layer, a separator layer, a negative electrode active material layer, and a negative electrode collector layer are contained in this order within an exterior body filled with a non-aqueous electrolyte solution.

[0041] When the lithium ion secondary battery of the present disclosure is an all-solid-state lithium ion secondary battery, the lithium ion secondary battery may have a structure in which a laminate in which, for example, a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer, and a negative electrode current collector layer are laminated in this order is housed in an exterior body. The inside of the exterior body may be under reduced pressure or in an atmosphere that is inert to the components constituting each layer of the laminate.

[0042] The lithium ion secondary battery of the present disclosure may be an all-solid-state battery that utilizes a deposition-dissolution reaction of metallic lithium as the negative electrode reaction.

[0043] Here, the "all-solid-state battery utilizing a deposition-dissolution reaction of metallic lithium as a negative electrode reaction" refers to an all-solid-state battery in which metallic lithium is deposited between the solid electrolyte layer and the negative electrode current collector layer as at least a part of the battery reaction during charging of the all-solid-state battery, and the metallic lithium dissolves during discharging. Such an all-solid-state battery may have a structure having, for example, a positive electrode current collector layer, a positive electrode active material layer, a solid electrolyte layer, a metallic lithium layer, and a negative electrode current collector layer in this order in a charged state.

[0044] In these lithium ion secondary batteries described above, the positive electrode current collector layer, the solid electrolyte layer, the separator layer, the negative electrode active material layer, the metallic lithium layer, the negative electrode current collector layer, and the exterior body can each be any known material used in those types of lithium ion secondary batteries.

[0045] Fig. 1 is a schematic diagram of an all-solid-state secondary battery according to a first embodiment of the present disclosure. Note that Fig. 1 is not intended to limit the lithium-ion secondary battery of the present disclosure.

[0046] As shown in Fig. 1, the lithium ion secondary battery 1 according to the first embodiment of the present disclosure may have a structure in which a positive electrode layer 10 having a positive electrode collector layer 11 and a positive electrode active material layer 12 disposed on the positive electrode collector layer 11, a separator layer 20, and a negative electrode layer 30 having a negative electrode collector layer 31 and a negative electrode active material layer 32 disposed on the negative electrode collector layer 31 are housed in an exterior body 100 filled with an electrolyte solution 40. Here, the positive electrode active material layer 12 contains the positive electrode active material of the present disclosure. Note that Fig. 1 is not intended to limit the present disclosure. EXAMPLES

[0047] Examples 1 to 5 and Comparative Examples 1 and 2 <Production of FeOHSO4 particles> As shown in Table 1 below, FeSO4·7H2O was heated from a starting temperature of 25°C at a prescribed heating rate for each example up to a maximum temperature of 280°C, and then maintained at the maximum temperature for 100 hours to produce the FeOHSO4 particles for each example.

[0048] <X-ray diffraction measurement> X-ray diffraction measurements using CuKα were performed on the FeOHSO4 particles of each example, and the X-ray diffraction spectrum shown in Figure 2 was obtained. Note that, although only Examples 1 and 5 and Comparative Example 1 are shown in Figure 2, measurements were also performed on the other examples.

[0049] Background processing was performed on the X-ray diffraction spectrum, and the maximum value of the peak confirmed at 34.5° ≦ 2θ ≦ 35.5° was defined as I a The maximum value of the peak observed at 33.5° ≤ θ < 34.5° is I b and the peak intensity ratio I b / I a was calculated.

[0050] The calculation results are shown in Table 1.

[0051] <Charge / Discharge Test> A coin-type lithium ion secondary battery was manufactured using the FeOHSO4 particles of each example as a positive electrode active material. Specifically, the coin-type lithium ion secondary battery of each example was manufactured as follows.

[0052] The FeOHSO4 particles of each example were mixed with acetylene black, polyvinylidene fluoride (PVdF), and N-methyl-2-pyrrolidone to prepare a positive electrode active material slurry. In the positive electrode active material slurry, the ratio (wt%) of the FeOHSO4 particles, acetylene black, and PVdF was 75:20:5.

[0053] The positive electrode active material slurry was applied by a doctor blade method onto an aluminum foil serving as a positive electrode current collector, dried at 80°C, and then rolled with a press to form a positive electrode current collector with a coating weight of 3 mg / cm. 2 Thus, a positive electrode active material layer having a thickness of 15 μm was obtained.

[0054] On the other hand, metallic lithium was prepared as a negative electrode active material layer.

[0055] In addition, a non-aqueous electrolyte solution was prepared by dissolving lithium salt (LiPF6) in a solution in which ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a ratio of 3:3:4 (volume ratio) to give a concentration of 1 mol / L.

[0056] As the separator layer, a laminated porous film of a polypropylene porous film and a polyethylene porous film was prepared.

[0057] A 2032-type coin cell container made of stainless steel foil was prepared, and a positive electrode active material layer, a separator, and a negative electrode active material layer were laminated in this order and housed therein.

[0058] The separator was impregnated with the non-aqueous electrolyte to prepare a coin-type lithium secondary battery.

[0059] For each of the obtained coin-type lithium secondary batteries, a cycle of constant current discharge at 0.1 C to a lower limit voltage of 2.0 V with an actual capacity of 140 mAh / g and then constant current charging at 0.1 C to an upper limit voltage of 4.5 V was repeated three times.

[0060] The discharge capacity in the third constant current discharge is shown in Table 1 below.

[0061] <result> Manufacturing conditions and test results for each example (peak intensity ratio I b / I a and discharge capacity) are shown in Table 1. The peak intensity ratio I b / I a The relationship between the charge and discharge capacity is shown in Table 3.

[0062] [Table 1]

[0063] As shown in Table 1 and FIG. 2, in Examples 1 to 5 in which the heating rates in the firing were 0.1° C. / min, 0.5° C. / min, 1.0° C. / min, 1.5° C. / min, and 3.0° C. / min, respectively, the peak intensity ratios I b / I a were 0.005, 0.004, 0.034, 0.101, and 0.203, respectively. This indicates that the peak derived from the FeOHSO4 crystal plane orientation (-122) is significantly larger than the peak derived from the FeSO4 crystal plane orientation (200). Also, referring to FIG. 2, it can be seen that in Examples 1 and 5, the peak derived from the FeSO4 crystal plane orientation (200), i.e., the peak confirmed within the range of 34.5°≦2θ≦35.5°, is very small.

[0064] In contrast, in Comparative Examples 1 and 2 in which the heating rates in the firing were 5.0°C / min and 10.0 / min, the peak intensity ratios I b / I awere 0.430 and 0.588, respectively, which were larger than those of the other Examples. Also, referring to Fig. 2, a large peak derived from the crystal plane orientation (200) of FeSO4 was confirmed in Comparative Example 1.

[0065] Moreover, the discharge capacities of the coin-type lithium secondary batteries using the FeOHSO4 particles of Examples 1 to 5 were 142.5mAh / g, 141.3mAh / g, 138.5mAh / g, 136.3mAh / g, and 132.9mAh / g, respectively, all of which were high values.

[0066] On the other hand, the discharge capacities of the coin-type lithium secondary batteries using the FeOHSO4 particles of Comparative Examples 1 and 2 were 117.4 mAh / g and 115.9 mAh / g, respectively, which were significantly lower than the discharge capacities of the coin-type lithium secondary batteries using the FeOHSO4 particles of Examples 1 to 5.

[0067] In addition, referring to FIG. 3, the peak intensity ratio I b / I a When the value of the α-type charge-discharge current (αTCV) was below 0.430, the discharge capacity tended to become particularly large. [Explanation of symbols]

[0068] 1. Lithium-ion secondary battery 10 Positive electrode layer 11 Positive electrode current collector layer 12 Cathode active material layer 20 Separator layer 30 Negative electrode body layer 31 Negative electrode current collector layer 32 Negative electrode active material layer 40 Electrolyte

Claims

1. FeOHSO, comprising a step of calcining iron sulfate hydrate at a heating rate of 0.5 ° C. / min or less and a maximum reaching temperature of 400 ° C. or less. 4 A method for producing particles.

2. 2. The method of claim 1, wherein the hydrated iron sulfate is iron sulfate heptahydrate.

3. The method according to claim 1 or 2, wherein the firing step includes maintaining the temperature for 10 hours to 300 hours after raising the temperature to the maximum temperature.

4. The method according to claim 3, wherein the maximum temperature is within a range of 100°C to 300°C.

5. The method according to any one of claims 1 to 4, wherein the calcination step is carried out under air atmosphere.

6. FeOHSO 4 The particles have a peak intensity (I a ) with respect to the peak intensity at 33.5°≦2θ<34.5° (I b ) ratio (I b / I a 6. The method of claim 1, wherein the n-th order is less than 0.

430.

7. FeOHSO 4 The method according to any one of claims 1 to 6, wherein the particles are a positive electrode active material for a lithium ion secondary battery.

Citation Information

Patent Citations

  • Preparation method of alkaline ferric sulfate anode material for lithium ion battery and electrodes

    CN103441272A

  • Catalyst for alkylation of isoalkane

    JP1999000560A

  • Positive electrode active material for lithium secondary battery and lithium secondary battery

    JP2014017154A

  • Positive electrode active material for lithium secondary battery, method for producing positive electrode active material for lithium secondary battery, and lithium secondary battery

    JP2014017157A

  • Method for reducing arsenic content in arsenic-bearing gold material

    US20180258510A1